Palliative Care and Ending of Life (EoL) Decision Making - Views and Attitude of MBBS & Nursing Students and paramedical staff - Kaur, Arshpreet; Singh, Vanshu; Jagtap, Charvi; Goyal, Mayank; Bhakar, Vikhayat; Ojha, Snehil; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Knowledge, perception, and attitudes toward palliative care and end-of-life (EoL) decision making vary among healthcare trainees and staff, and can influence patient care quality. This study aims to assess perceptions and attitudes among MBBS students & interns, nursing students, and paramedical staff in two medical colleges and their hospitals. Methods: Cross-sectional survey (n = 300) using a structured, pre-tested questionnaire covering knowledge of palliative care, attitudes toward EoL decisions (withholding/withdrawing life-sustaining treatment, do-not-resuscitate orders), self-perceived preparedness, and barriers to providing palliative care. Data will be analyzed using descriptive statistics, group comparisons (Chi-square, ANOVA), and multivariable logistic regression to identify factors associated with favorable attitude toward EoL decision making. Results: (The Results below are example/simulated outputs showing how findings should be presented. Replace with your collected data.) Overall, 62% of participants had moderate to good knowledge of palliative care. Favorable attitudes toward discussing EoL issues were more frequent among nursing students (72%) and MBBS interns (68%) than paramedical staff (48%). Major barriers reported were lack of training (81%), cultural/religious concerns (64%), and fear of legal consequences (53%). Conclusions: Training gaps and legal/ethical concerns are major barriers to optimal palliative care delivery. Incorporating structured palliative care education across curricula and hospital in-service training is recommended.